(untitled) (Fiep Bulletin - online, 2013)
The chronic diseases has not have been increasing its prevalence in Brazil and in the world, and among them the cardiovascular diseases stand out for having the Systemic Arterial Your hypertension risk main factor, that for being one worsen multifatorial, being them factors of modifiable risk or not, finds in the masculine group the being that suffers more the influence of these factors, because it is the remotest group in the health services. To select the variables and to identify its relation with the variable dependent: Control of the arterial pressure, applied in the Regression Logistics model. The descriptive analysis presents a masculine group in its majority with not controlled Pressure (59,2%), senior (64,0%), schooled (66,7%), living with company (93,3%), no (70,7%), not smoker (80,0%), not sedentary (50,7%), in overweight/obesity (53,3%) and not ethyl (84,0%). The model fitting presented as explanatory variables for PA Control, adopting itself a reliable interval of 95% and one to=0,05, obesity (p-value =0,047) and race (p-value =0,036). The relevance meets in the fact that, the health actions are more focused in the factors of modifiable risk as smoker, ethyl, sedentarism, and with the results presented by the model evidences the need to if establish programs, strengthen partnerships, assistances and turns in the health services of the basic attention, that propitiate a better welcoming to the man with more specific activities for the obesity control.